Aspects of «Cocktail» cytochrome P450 activity determination methods application with the view of drug treatment rationalization - E. . Egorenkov; V. . Smirnov; A. . Litvin; G. . Kolyvanov; G. . Ramenskaya (Фармакокинетика и Фармакодинамика)
Rational pharmacotherapy is understood as intelligent drug combination and dosage adjustment for the purpose of drug adverse events development risk minimization and achievement of suitable therapeutical effect. One of the main factors affecting on drug potency is activity of biotransformation system. In this work, a review of promising "cocktail" method of biotransformation enzymes activity determination in vivo is given.